2018
DOI: 10.1088/2057-1976/aac9fe
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating of Antibody-functionalized Carbon Nanotubes as a Feasible Cancer Treatment

Abstract: Polyclonal antibody/carbon nanotube (CNT) conjugates have been prepared through a di-imide activated amidation process using partially oxidized CNTs. The antibody/nanotube conjugate was used as a microwave absorber with selective affinity for the cell receptor CD44, overexpressed on the surface of PC3 prostate cancer cells. Unlike the most common protocols involving thermic ablation by infrared radiation, microwaves offer a significant higher penetration depth, with instant localized heating when combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…This effect causes injuries to the mitochondria and then apoptosis, resulting in a decrease in tumor volume and an improved survival in mouse models https://doi.org/10.1007/s40820-020-00537-8 © The authors [93]. Beckler confirmed the efficiency of carbon nanotubes with MW for anticancer therapy with multi-walled carbon nanotubes decorated with antiCD44 antibody to target prostate cancer [92].…”
Section: Microwave Responding Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect causes injuries to the mitochondria and then apoptosis, resulting in a decrease in tumor volume and an improved survival in mouse models https://doi.org/10.1007/s40820-020-00537-8 © The authors [93]. Beckler confirmed the efficiency of carbon nanotubes with MW for anticancer therapy with multi-walled carbon nanotubes decorated with antiCD44 antibody to target prostate cancer [92].…”
Section: Microwave Responding Npsmentioning
confidence: 99%
“…A possibility is to employ nanomaterials that, in synergy with MWs, improve the temperature absorbing energy [ 21 ] and may promote a Joule heating effect [ 92 ]. Additionally, it is reported that some nanotools, e.g., iron oxide NPs and carbon nanotubes, are able to produce shock waves under a MW input, provoking a mechanical stimulation of the cells [ 93 , 94 ].…”
Section: Microwave Responding Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can prevent normal and healthy cells from dying. 21,23,120,121 Biopersistence and Biodegradation CNTs are known to persist in lungs, leading to injury of the organ. Subchronic exposure of MWCNTs to the lungs of in vivo models through inhalation displayed higher retention half times, with the increases in retention being time-and concentrationdependent.…”
Section: Routes Of Administrationmentioning
confidence: 99%
“…Previous publications have put forth theoretical models to describe RF interactions with CNTs to produce heating and local field enhancement [8]. Additionally, several studies attempted to experimentally validate the utility of CNTs for RFA and MH [9][10][11]. Despite these reports, a significant challenge of applying CNTs for RFA and MH in vivo arises from nonspecific RF absorption by soft tissue, especially that by the water molecules and ions therein.…”
Section: Introductionmentioning
confidence: 99%